Dissemination of multi-resistant bacterial strains associated with the community and the hospital: an overview of public health risk - Jessica Dantas de Lucena, Bruna; Lorrany de Souza Morais, Emanuelly; Vitoria Gomes de Sousa, Sarah (Seven Editora, 2023)
The evolutionary process of microorganisms favors their survival in hyspid environments. Annually thousands of lives are claimed as a result of resistant bacteria, pathogens previously restricted to the hospital environment can now be easily found in the community. The main objective of the present study is to provide information on the microbiological dissemination pathways in the community, focusing on food and surfaces. The study is a systematic review, in which several studies published in journals originally in the English language were analyzed and evaluated, during the period from 2017 to 2022. In order to select the studies with the greatest scientific evidence, favoring controlled and randomized clinical trials, in addition to systematic and bibliographic reviews. The lack of biosecurity when handling products of animal origin is a major risk to public health, these failures involve not washing hands after handling, using the same container for preparing or storing raw meat to ingest the cooked meat, without due prior cleaning. According to a survey, approximately 90% of the cell phones of health professionals were colonized by some microorganism, where 14% represented pathogenic and infection- causing bacteria. The dissemination of knowledge about hygiene and daily care is fundamental in controlling the transmission and spread of multidrug- resistant microorganisms. This action is capable of saving lives and helping the health system to develop more effective treatments, thus, research in the field of bacteriology is essential to improve academic and community knowledge. DOI: 10.56238/pacfdnsv1-016